2014
DOI: 10.1586/17474086.2014.976551
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and monitoring of core-binding factor acute myeloid leukemia: current and emerging factors

Abstract: Core-binding factor acute myeloid leukemia (CBF-AML) - including AML with t(8;21) and AML with inv(16) - accounts for about 15% of adult AML and is associated with a relatively favorable prognosis. Nonetheless, relapse incidence may reach 40% in these patients. In this context, identification of prognostic markers is considered of great interest. Due to similarities between their molecular and prognostic features, t(8;21) and inv(16)-AML are usually grouped and reported together in clinical studies. However, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 136 publications
1
17
1
2
Order By: Relevance
“…Patients with t-AML are more prone to a poor prognosis and cytogenetic findings. Core binding factor abnormalities are associated with an improved outcome in patients with AML (39)(40)(41). However, in the present cohort, t (15,17) appeared to have a good effect on the outcome of disease, even in patients with t-AML (42)(43)(44)(45).…”
Section: Characteristiccontrasting
confidence: 63%
“…Patients with t-AML are more prone to a poor prognosis and cytogenetic findings. Core binding factor abnormalities are associated with an improved outcome in patients with AML (39)(40)(41). However, in the present cohort, t (15,17) appeared to have a good effect on the outcome of disease, even in patients with t-AML (42)(43)(44)(45).…”
Section: Characteristiccontrasting
confidence: 63%
“…However, the molecular genetic abnormalities potentially explaining differences between these 2 subtypes of AML have not been explored in detail. Although implication of TK pathways in CBF AML leukemogenesis has been widely studied, 15 only a few reports have identified cooperating mutations in CBF AML outside of TK pathway alterations. Although the "2-hit model" of leukemogenesis mentioned earlier is biologically relevant, it is impossible to ignore the multitude of genetic and epigenetic aberrations that have recently been described in human leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with t(8;21) or inv (16) AML differ with respect to several biological and clinical features. 15 Morphologically, patients with t(8;21) AML frequently present with the French-American-British morphological subtype M2 or AML with maturation, whereas patients with inv(16) more often are diagnosed with the French-AmericanBritish subtype M4Eo or acute myelomonocytic leukemia with abnormal marrow eosinophils. 16 Moreover, gene expression profiling of CBF AML segregate t(8;21) and inv(16) patients into distinct subgroups, 17 reflecting different pathways activated in each subtype of CBF AML.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, several studies have identified that ASXL1 and ASXL2 mutations are enriched in a very specific subset of AML, AML with t(8;21) (Huether et al 2014; Duployez et al 2015b), which represent ~10% of all AML. ASXL family member mutations occur in ~30% of pediatric and adult t(8;21) AML patients (Figs.…”
Section: Discovery Of Mutations In Asxl Gene Family Members In Cancermentioning
confidence: 99%